2019
DOI: 10.1007/s10620-019-05587-6
|View full text |Cite
|
Sign up to set email alerts
|

Mailed Outreach Is Superior to Usual Care Alone for Colorectal Cancer Screening in the USA: A Systematic Review and Meta-analysis

Abstract: Background: Mailed outreach promoting colorectal cancer (CRC) screening with a stool blood test kit may increase participation, but magnitude and consistency of benefit of this intervention strategy is uncertain. Aim: Conduct a systematic review and meta-analysis of randomized controlled trials (RCTs) comparing mailed outreach offering stool tests to usual care, clinic-based screening offers on CRC screening uptake in the United States. Methods: We performed a systematic literature search of 5 databases for RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 31 publications
(14 reference statements)
1
59
0
Order By: Relevance
“…Multivariate Model for Colonoscopy Completion within 1 Year After FIT Return With a Positive FIT (N = 164) 1,2. …”
mentioning
confidence: 99%
“…Multivariate Model for Colonoscopy Completion within 1 Year After FIT Return With a Positive FIT (N = 164) 1,2. …”
mentioning
confidence: 99%
“…Therefore, current gaps in the uptake of CRC screening could be addressed by using FOBT/FIT in widespread public health programs. Some population‐based interventions have found FOBT/FIT to be particularly effective in boosting CRC screening uptake when kits are mailed to homes along with instructions and educational packages . Similarly, a systematic review revealed that outreach interventions including those utilizing mailed FOBT kits improved CRC screening in Canada, and several European countries .…”
Section: Discussionmentioning
confidence: 99%
“…15 be particularly effective in boosting CRC screening uptake when kits are mailed to homes along with instructions and educational packages. 46,48,51 Similarly, a systematic review revealed that outreach interventions including those utilizing mailed FOBT kits improved CRC screening in Canada, and several European countries. 52 This initiative should be tested for potential scalability at the national level.…”
Section: Model 2 (Sociodemographic Plus Crc Risk Factors)mentioning
confidence: 99%
“…Evidence-based strategies for improving screening include mailed outreach offering fecal immunochemical test, offering more than just 1 screening option, culturally tailored patient navigation, 1-on-1 education, and patient and clinician reminders, with many having been tested in racial/ethnic minority groups. [10][11][12][13][14][15][16][17][18][19] These interventions seem to be most successful when implemented as multiple, rather than single components. 20 Revisiting the findings of May et al 4 emphasizes that the commitment to investing in interventions to achieve health equity in CRC screening will need to be robust (Figure 1).…”
mentioning
confidence: 99%